Article RETRACTED due to manipulation by the authors A systematic review and meta-analysis of the impact of muscle fatigue on the biomechanics of joint range of motion (ROM) in badminton - Ahmad Chaeroni; Kamal Talib; Mohd Nizam Lani; Mert Kurnaz; Bekir Erhan Orhan; Endang Sepdanius; Nurettin Konar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aims to evaluate the impact of muscle fatigue on the biomechanics of joint range of motion (ROM) in badminton athletes through a systematic literature review and meta-analysis. Muscle fatigue can affect athletic performance, particularly in dynamic movements such as lunges and smashes. Using the Systematic Literature Review (SLR) method and PRISMA, this study identified and analyzed 9 scientific articles from the Scopus and WoS databases published between 2019 and 2024. Meta-analysis was conducted by calculating the Standardized Mean Difference (SMD) and the 95% confidence interval (95% CI). The results showed that ROM in the hip joint significantly decreased after fatigue, with an SMD of -0.56 (95% CI: -0.76 to -0.36), which increases the risk of adductor and abductor injuries. On the other hand, ankle ROM showed no significant changes between pre-fatigue and post-fatigue conditions (SMD = 0.06, 95% CI: -0.13 to 0.25). For the knee joint, significant heterogeneity was found among studies with an I² value of 52% and an overall SMD of -0.01 (95% CI: -0.28 to 0.26), indicating that the effect of fatigue on knee ROM was inconsistent. This study concludes that muscle fatigue plays a crucial role in biomechanical changes that may increase the risk of injury in badminton athletes. Coaches are advised to implement interventions such as dynamic stretching and foam rolling to reduce muscle stiffness and maintain optimal ROM during matches. This study provides a critical scientific basis for developing evidence-based injury prevention programs.